Association of combined pulmonary fibrosis and emphysema in rheumatoid arthritis with high titer of rheumatoid factor and autoimmunity to the lung - Ma, Aiping; Huang, Renliang; Guo, Jiaxi; Wang, Guangdong; Huang, Heqing; Li, Xinze; Zhong, Shan; Huang, Yan; Lin, Shaowei; Lin, Yikai; Zhou, Qiaomiao; Krauss-Etschmann, Susanne; et al. (Frontiers in Immunology, 2025)
BackgroundCombined pulmonary fibrosis and emphysema (CPFE) commonly coexists with connective tissue diseases (CTD), such as rheumatoid arthritis (RA). However, the risk factors contributing to the development of CTD-CPFE remain largely unidentified. This study aimed to characterize CPFE using a large cohort of consecutive RA patients and to elucidate potential risk factors associated with RA- CPFE development.MethodsA total of 976 RA patients were enrolled in this cross-sectional study to characterize RA-CPFE. Multiple logistic analyses were conducted to identify potential risk factors for RA-CPFE development. Patient IgG and IgM autoantibodies to primary human bronchial epithelial cells (HBEC) from healthy donors were assessed using flow cytometry.FindingsAmong the 976 RA patients, 414 (42.4%) developed interstitial lung disease (ILD), with 74 (7.6%) experiencing CPFE. In comparison to RA-CPFE patients with centrilobular or paraseptal emphysema, those with panacinar emphysema had higher emphysema scores and decreased pulmonary function parameters. Multiple logistic regression analysis revealed that male gender, cigarette smoking, occupational exposure to dust, high ILD score, high rheumatoid factor (RF) titers, and the presence of anti-SSA were associated with an increased risk for RA-CPFE. Additionally, levels of IgG and IgM autoantibodies to HBEC were elevated in RA-CPFE patients compared to healthy controls and positively correlated with RF levels.InterpretationThis study is the first to demonstrate the association of RA-CPFE with high titer of RF and the presence of autoantibodies against HBEC, suggesting a link between autoimmunity to the lung and RA-CPFE.